Priming creativity: Doing math reduces creativity and happiness whereas playing short online games enhance them - Haase, Jennifer; Hanel, Paul H. P. (Frontiers in Education, 2022)
Creative thinking is an indispensable cognitive skill that is becoming increasingly important. In the present research, we tested the impact of games on creativity and emotions in a between-subject online experiment with four conditions (N = 658). 1: participants played a simple puzzle game that allowed many solutions (priming divergent thinking); 2: participants played a short game that required one fitting solution (priming convergent thinking); 3: participants performed mental arithmetic; 4: passive control condition. Results show that divergent and convergent creativity were higher after playing games and lower after mental arithmetic. Positive emotions did not function as a mediator, even though they were also heightened after playing the games and lower after mental arithmetic. However, contrary to previous research, we found no direct effect of emotions, creative self-efficacy, and growth- vs. fixed on creative performance. We discuss practical implications for digital learning and application settings.